Experimental Research of Permanent Magnet Synchronous Traction Motor for Metro Vehicle - LIU Kean; XU Junfeng; WEN Yuliang; HE Yaping; LIU Xiong; ZHANG Chaoyang (Kongzhi Yu Xinxi Jishu)
Based on the introduction of traction system of metro vehicle, the mathematic model for permanent magnet synchronous motor (PMSM) is elaborated. According to the characteristics of PMSM and the metro vehicle operation, the constant torque control, flux weakening control and restart control with motor rotation have been realized on the ground test platform. The experiment results have been given and the system efficiency has been compared with induction motor traction system, which proves that the PMSM traction has the merit of high efficiency. The ground test of PMSM traction system establishes a firm foundation for the application on metro vehicle.